Event‐related potential indices of congruency sequence effects without feature integration or contingency learning confounds. (8th February 2016) - Larson, Michael J.; Clayson, Peter E.; Kirwan, C. Brock; Weissman, Daniel H.
Abstract: The congruency effect in Stroop‐like tasks (i.e., increased response time and reduced accuracy in incongruent relative to congruent trials) is often smaller when the previous trial was incongruent as compared to congruent. This congruency sequence effect (CSE) is thought to reflect cognitive control processes that shift attention to the target and/or modulate the response engendered by the distracter differently after incongruent relative to congruent trials. The neural signatures of CSEs are therefore usually attributed to cognitive control processes that minimize distraction from irrelevant stimuli. However, CSEs in previous functional neuroimaging studies were ubiquitously confounded with feature integration and/or contingency learning processes. We therefore investigated whether a neural CSE can be observed without such confounds in a group of healthy young adults ( n = 56). To this end, we combined a prime‐probe task that lacks such confounds with high‐density ERPs to identify, for the first time, the neural time course of confound‐minimized CSEs. Replicating recent behavioral findings, we observed strong CSEs in this task for mean response time and mean accuracy. Critically, conceptually replicating prior ERP results from confounded tasks, we also observed a CSE in both the parietal conflict slow potential (conflict SP) and the frontomedial N450. These findings indicate for the first time that neural CSEs as indexed by ERPs can be observed without the typical confounds. More broadly, the present study provides a confound‐minimized protocol that will help future researchers to better isolate the neural bases of control processes that minimize distraction from irrelevant stimuli.